Motivation of Elderly Congregations as Tarekat Syattariyah Member - M. Baqri (UIN Sjech M. Djamil Djambek Bukittinggi, 2023)
Motivation of Elderly Congregants to Join the Sayttariyah Congregation at the Jamiatul Mukminin Sintuak Islamic Boarding School Surau, Padang Pariaman Regency. The motivation for the elderly congregation to join the Syattariyah order is the 40 prayers which are held in congregation for 40 days starting on the last 20 days of the month of Rajab until the 20th day of the month of Sha'ban. Go on a pilgrimage to the graves of previous teachers, Zikir, and Wirid. The motivation of the elderly congregation is an actualization of the teachings of the Syattariyah congregation which follows and carries out actions according to the teachings of the Prophet Muhammad. This article examines the motivation of elderly congregation members to join the Syattariyah order. Using qualitative methods, this is done through observation. This article examines the motivation of elderly congregation members to join the Syattariyah order at the Jamiatul Mukminin Sintuak Islamic Boarding School, Padang Pariaman Regency, there are 4 things, including: (1) praying 40 prayers, encouragement in a hadith, to seek provisions in the afterlife to avoid hellfire. (2). Pilgrimage, as a religious tourism that can please the congregation and to pray for scholars who have contributed to sharing their knowledge, to tabarruk or obtain blessings, (3). Dhikr, which can calm the heart, eliminate feelings of distress and anxiety, an effort to taqorrup to Allah SWT. (4). Wirid, which can increase insight into religious knowledge.